Extraction and Perconcentration of Lead(II) using Octadecyl Bonded Silica Cartridge and Its Determination by Flame Atomic Absorption Spectrometry - Moghimi, Ali; Esfanjani, Shahimeh; Mazloomifar, Hefzollah (Asian Journal of Chemistry, 2012)
A simple method has been developed for the preconcentration of lead(II) based on the adsorption of its 1-(2-pyridyl azo)-2-naphthol complex on a octadecyl bonded silica cartridges. The influence of acidity, eluting agents, stability of the column, sample volume and interfering ions has been investigated. The adsorbed complex could be eluted using environmentally benign 4 M HNO3 and the concentration of lead(II) was determined by flame atomic absorption spectrometry. A detection limit of 50 μg L-1 could be achieved and the developed procedure was successfully applied for the determination of lead(II) in tap water and waste water samples.